Hepatoprotective potential of Azima tetracantha and Tribulus terrestris on ferrous sulfate-induced toxicity in rat (Bangladesh Journal of Pharmacology, 2013)
The present study is to evaluate the antihepatotoxic effect of hydroalcoholic extract of leaf powder of Azima tetracantha and the fruit powder of Tribulus terrestris. Ferrous sulfate was used to induce hepatotoxicity and Silymarin was used as a standard drug. The level of biochemical parameters such as protein, albumin, globulin, HDL, vitamin E, superoxide dismutase and catalase were observed to be decreased and the level of glucose, LDL, VLDL, bilirubin, cholesterol, triglycerides, alkaline phosphatase and TBARS were increased in hepatotoxicity-induced rats. Retrieval of liver parameters to normal level was obtained after the oral administration of herbal drugs. Histopathological studies revealed diminished hepatocellular injury in the herbal drugs treated rats. As a conclusion hydro alcoholic extract of leaf powder of A. tetracantha and fruit powder of T. terrestris were possesses significant hepatoprotective activity.